2010
DOI: 10.1038/hr.2010.126
|View full text |Cite
|
Sign up to set email alerts
|

Brachial-ankle pulse wave velocity as a risk stratification index for the short-term prognosis of type 2 diabetic patients with coronary artery disease

Abstract: , the Shinken Database Study GroupThe incidence of diabetes is increasing, and the disease has become an important predictor of prognosis in patients with coronary artery disease (CAD), although adverse events often occur without warning. Thus, risk stratification of diabetic CAD patients is important for secondary prevention. This study tests the hypothesis that brachial-ankle pulse wave velocity (baPWV), a marker for arterial stiffness obtained by simple and noninvasive automated devices, can be a risk strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 45 publications
1
58
0
Order By: Relevance
“…In the present study, CAD patients with baPWV ≥1731 cm/s had significantly more cardiovascular events than those in patients with baPWV <1731 cm/s. In addition, baPWV ≥1731 cm/s was a significant predictor of increased risk of cardiovascular events independent of conventional cardiovascular risk factors, LVEF, and BNP (hazard ratio, 1.86; 95% CI, 1.01–3.44; P =0.004 for the first primary outcomes in Model 1; hazard ratio, 2.19; 95% CI, 1.23–3.90; P =0.008 for the second primary outcomes in Model 1; hazard ratio, 1.99; 95% CI, 1.04–3.82; P =0.04 for the first primary outcomes in Model 2; hazard ratio, 2.17; 95% CI, 1.18–4.00; P =0.01 for the second primary outcomes in Model 2), being consistent with the results of a previous study showing that baPWV ≥1730 cm/s was independently associated with increased risk of cardiovascular events in patients with type 2 diabetes mellitus with CAD 36. These findings suggest that measurement of baPWV in patients with CAD might be clinically useful for identifying individuals who have increased arterial stiffness and who are at high risk for recurrent cardiovascular events.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, CAD patients with baPWV ≥1731 cm/s had significantly more cardiovascular events than those in patients with baPWV <1731 cm/s. In addition, baPWV ≥1731 cm/s was a significant predictor of increased risk of cardiovascular events independent of conventional cardiovascular risk factors, LVEF, and BNP (hazard ratio, 1.86; 95% CI, 1.01–3.44; P =0.004 for the first primary outcomes in Model 1; hazard ratio, 2.19; 95% CI, 1.23–3.90; P =0.008 for the second primary outcomes in Model 1; hazard ratio, 1.99; 95% CI, 1.04–3.82; P =0.04 for the first primary outcomes in Model 2; hazard ratio, 2.17; 95% CI, 1.18–4.00; P =0.01 for the second primary outcomes in Model 2), being consistent with the results of a previous study showing that baPWV ≥1730 cm/s was independently associated with increased risk of cardiovascular events in patients with type 2 diabetes mellitus with CAD 36. These findings suggest that measurement of baPWV in patients with CAD might be clinically useful for identifying individuals who have increased arterial stiffness and who are at high risk for recurrent cardiovascular events.…”
Section: Discussionsupporting
confidence: 90%
“…Several lines of evidence have demonstrated that baPWV could be used not only as an index of atrial stiffness but also as a prognostic marker of cardiovascular events 35. However, there have been few studies in which the predictive value of baPWV in patients with established CAD was investigated 30, 36. In the present study, CAD patients with baPWV ≥1731 cm/s had significantly more cardiovascular events than those in patients with baPWV <1731 cm/s.…”
Section: Discussionmentioning
confidence: 45%
“…One studied baPWV in hemodialysis patients, 16 two were conducted in the general population 17,18 and the remaining two were conducted in patients with acute coronary syndrome 21 or diabetes accompanied by coronary artery disease. 22 Although the cohorts differed extensively, the suggested cut off value for poor cardiovascular prognosis ranged from 1700 to 1963 cm s -1 . In light of the previous and present results, we propose that a baPWV of 18 m s -1 should be considered a tentative marker for organ damage.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, pulse wave velocity (PWV) has been a widely accepted noninvasive measurement of arterial stiffness (Laurent et al 2006) and its value in predicting negative cardiovascular events (including both CAD and other cardiovascular diseases) has been extensively demonstrated (Sugawara et al 2005;Tomiyama et al 2005;Meguro et al 2009;Nakamura et al 2010;Munakata et al 2012;Vlachopoulos et al 2012). Nonetheless, the use of PWV measurement remains to be unsuitable for the patient screening or risk stratifica-tion in routine clinical practice due to the relatively high cost, requirement of expertise operation and long measurement time.…”
Section: Introductionmentioning
confidence: 99%